Pencegahan Demam Berdarah Dengue (DBD) Melalui Upaya Promosi Kesehatan Pemanfaatan Tanaman Kemangi (Ocimum basilicum) dan Ikan Cupang (Betta splendens) Sebagai Agen Pengendalian Hayati Jentik Nyamuk - Dita Amanda; Sari Prayudeni; Devina Putri; Brilliant Prameswari; Windy Alya Agustine; Debby Ramadani Kusnadi; Zainullah Nor Wahed (Jurnal Pengabdian Masyarakat (JUDIMAS), 2026)
Dengue Hemorrhagic Fever (DHF) remains a serious public health problem in Banyuwangi Regency, with cases surging to 550 and 19 fatalities recorded in 2024. A community service program entitled " Prevention of Dengue Hemorrhagic Fever (DHF) Through Health Promotion Efforts Utilizing Basil Plants (Ocimum basilicum) and Betta Fish (Betta splendens) as Biological Control Agents for Mosquito Larvae" was conducted from January 15–22, 2025 at Ma'had MTsN 1 Banyuwangi, Giri District, involving 40 students from the Junior Red Cross (PMR) and School Health Unit (UKS). This program aimed to improve students' knowledge of DHF prevention through the 3M Plus Mosquito Nest Eradication (PSN) method and the utilization of Family Medicinal Plants (TOGA). A pre-experimental approach with a one group pretest-posttest design was employed, encompassing interactive lectures, educational video screenings, direct planting demonstrations of basil (Ocimum basilicum) as a natural bioinsecticide, introduction of temefos powder (abate), and Siamese fighting fish (Betta splendens) as biological larvae control agents. Evaluation results demonstrated a highly significant improvement in knowledge, from 50% of participants achieving scores ≥80 in the pretest to 100% in the posttest. This program is expected to foster sustained 3M Plus behavior and empower participants as change agents in realizing a larvae-free school environment in Banyuwangi Regency. Keywords: Dengue Hemorrhagic Fever; Mosquito Nest Eradication; Family Medicinal Plants